(untitled) (Journal of Experimental and Clinical Anatomy, 2004)
Prostrate size viz; Prostate length, longitudinal thickness, transverse thickness and volume were measured by trans-abdominal ultrasound among selected 113 subjects in South East of Nigeria. The subjects ranged from age 15 to 85. The result showed statistically significant relationship between age and prostate size (P<0.01). It also established a normogram of the prostate sizes within the selected age groups.